Rebellious desire - Garwood, Julie; Copyright Paperback Collection (Library of Congress) (New York Pocket Books, 1986)
Of all the dukes in England, Jered Marcus Benton, the Duke of Bradford, was the wealthiest, most handsome-and most arrogant. And of all London's ladies, he wanted the tender obedience of only one-Caroline Richmond. She was a ravishing beauty from Boston with a mysterious past and a fiery spirit
1
Keywords: Love stories